2021
DOI: 10.1021/jacs.0c11008
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Single-Atom Ni Site Active toward Electrochemical CO2 Conversion to CO

Abstract: Electrocatalytic conversion of CO2 into value-added products offers a new paradigm for a sustainable carbon economy. For active CO2 electrolysis, the single-atom Ni catalyst has been proposed as promising from experiments, but an idealized Ni–N4 site shows an unfavorable energetics from theory, leading to many debates on the chemical nature responsible for high activity. To resolve this conundrum, here we investigated CO2 electrolysis of Ni sites with well-defined coordination, tetraphenylporphyrin (N4–TPP) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
82
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(84 citation statements)
references
References 52 publications
2
82
0
Order By: Relevance
“…As a proof of concept, we chose to evaluate the catalytic performance of the UHD-SACs in the electrochemical CO 2 reduction to carbon monoxide, an application where nickel single atoms demonstrate promising technical potential 35,36 . For the Ni 1 /NC catalyst, the only products detected are gas-phase CO and H 2 and no liquids in the voltage range from 0 to -1.15 V versus RHE.…”
Section: Enhanced Productivity Of Uhd-sacsmentioning
confidence: 99%
“…As a proof of concept, we chose to evaluate the catalytic performance of the UHD-SACs in the electrochemical CO 2 reduction to carbon monoxide, an application where nickel single atoms demonstrate promising technical potential 35,36 . For the Ni 1 /NC catalyst, the only products detected are gas-phase CO and H 2 and no liquids in the voltage range from 0 to -1.15 V versus RHE.…”
Section: Enhanced Productivity Of Uhd-sacsmentioning
confidence: 99%
“…In addition to metal phthalocyanines, some other molecular complexes, such as metal porphyrins, also have a defined M–N 4 structure. Kim et al reported carbon substrate supported Ni molecular complexes with two different porphyrins ligands, tetraphenylporphyrin (N 4 –TPP) and 21-oxatetraphenylporphyrin (N 3 O-TPP) 88 Spectroscopic and computational studies of Ni–N 4 -TPP and Ni(–Cl)–N 3 O-TPP revealed that the destruction of the ligand field symmetry could increase the redox potential from 0 to +1, leading to a better performance in the CO 2 RR. The additional ligand for the central atoms could also be a modification strategy to regulate the interfacial electronic structure from the axial direction.…”
Section: Design and Synthesis Of Sacs For The Co 2 Rrmentioning
confidence: 99%
“…[ 4 ] The recent implementation of SACs into CO 2 reduction has proven that the microenvironments and electronic properties of single‐atom active centers are essential for catalytic activity. [ 5 ] Up to now, pioneering work have reported several strategies to modulate the local structure of single‐atom active sites and compare their catalytic performance on CO 2 conversion, such as designing molecular catalysts, [ 6 ] carbonization of functionalized precursors, [ 7 ] or tuning coordination number of metal centers supported on metal organic layers. [ 8 ] Despite of these developments, these methods either suffered from tedious synthetic process or indirectly controlled SACs configuration at atomic level.…”
Section: Introductionmentioning
confidence: 99%